Agronomic performance of Humulus lupulus L. varieties cultivated in organic and conventional systems in São Paulo center-west, Brazil - Neves, Caio Scardini [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Fortuna, Gabriel Cássia [UNESP]; de Oliveira Gomes, Jordany Aparecida [UNESP]; Campos, Olivia Pak [UNESP] (FapUNIFESP (SciELO), 2023)
Hop is a multifunctional specie; however, a large part of its production is destined for the beer market. In Brazil, all hop demand is imported, which has aroused interest in national production. Genetic material and cultivation systems can influence hops production. Thus, this study evaluated morphological and productive performance of hop varieties grown under organic and conventional management in the central-west region of São Paulo, Brazil. The hop yard was installed in the experimental area of the FCA/UNESP (São Paulo State University, School of Agriculture) – Botucatu, in November 2018, the data were collected in second year of production. A randomized block design was adopted, in 2 x 5 Split-Plot, being the main factor: cultivation systems (organic and conventional), and secondary factor: hop varieties (Columbus, Chinook, Nugget, Cascade, and Hallertau Mittelfrüeh), with four blocks and four plants per plot. Crop-specific morphological and productive parameters were evaluated. The results showed no significant influence of cultivation systems in morphological parameters. Regarding the varieties, Chinook, Cascade, and Nugget stand out for cone length. Columbus, Chinook and Cascade showed higher yields when grown in organic system, obtaining 1100.66, 1088.27 and 940.40 g of cones per plant, respectively. While, Hallertau Mittelfrüeh variety was the least productive in both systems, in organic system with 160.50 g per plant production, and 267.84 g per plant in conventional system, and, also showing lower cycle compared to the others.
Desempenho agronômico de variedades de Humulus lupulus L. cultivadas em sistema orgânico e convencional no centro-oeste paulista, Brasil
Keywords: Brazilian hops; genetic materials; morphological and productive parameters; organic and conventional cultivation; tropical climate